Karakterisasi Mikrobiota Mulut Penghasil Senyawa Antimikroba: Laboratory Research - Ade Irma; Juniati Binti Lukman; Arafah Nurfadillah (Badan Riset dan Inovasi Nasional, 2022)
Microbes or microorganisms are organisms that have a size so small that they can only be seen with the help of a microscope. Microbes are widespread in nature and can be found anywhere. Mikroba can be settled in the soil, water, air, there is even one that is found in living beings (on living tissues). The microbiome is a community of microbes or microorganisms in this case bacteria, archae, fungi, viruses that live above or within other living organisms. The human-associated microbiome is called the microbiota. The presence of microbes in the body can cause interactions that are beneficial, detrimental or some are neutral in nature. The use of antibiotics whose nature is synthetic can cause a negative effect for health besides that it can also cause resistance properties. Therefore, it is necessary to have a type of antibiotic that comes from living beings. The sample used in this study was a bacterial isolate in the oral cavity (swab results) the next stage was characterization through biochemical tests. The results of characterization through biochemical tests showed that isolates of oral microbiota bacteria showed the species Streptococcus sp. which has the ability to produce antimicrobial compounds.